Literary Traditions: English in Malaysia and Singapore (Column 5) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
IT is possible that some of the writers who were born in the Malayan territory that now constitutes Malaysia chose to stay back in Singapore after the political separation between the two countries, or later moved to Singapore and other countries, because of the stiff policies on language and literature. Would Catherine Lim or Suchen Christine Lim have made Singapore their home if the hierarchic policies and privileging norms in matters of language and literature had not been adopted? I believe there is no clear answer to such a question, although there is room for conjecture that things might have been otherwise if Malaysia had adopted a more inclusivist and accommodating spirit in its definition of national literature. I recently took the opportunity of asking both Catherine Lim and Suchen Christine Lim as to why we should not consider them as Malaysian writers in the same way as we continue to view Shirley Lim as a Malaysian writer in spite of her emigration to and subsequent citizenship in the US, or as critics see Bharati Mukherjee as an Indian writer despite her domicile in the US. Suchen Christine Lim responded with considerable ambiguity, suggesting that she belonged to both (Malaysia and Singapore) and was grateful to both, because “one gave [her] life, the other gave [her] an upbringing.” Catherine Lim's response, however, was a more resounding “no.” I asked her that since she was born and educated in Malaysia and since she wrote about her childhood memories in Malaysia, wouldn't it be appropriate to consider her a Malaysian writer? Her reply was: I find it difficult to consider myself a 'Malaysian writer'rather than a 'Singaporean writer,' simply because I suppose my sense of being a Singaporean is so strong, Singapore being the country I have adopted, grown to love very much and will always be committed to. One is left to wonder if the status of English and English writing in the country has anything to do with Catherine Lim's such strong attachments for Singapore and a concomitant apathy towards the country that gave her life and provided shelter and protection for the first twenty eight years.